Accountability for violations of international humanitarian law essays in honour of Tim McCormack - Petrovic, Jadranka (Routledge research in the law of armed conflict, 2016)
International criminal adjudication, together with the prosecution and appropriate punishment of offenders at a national level, remains the most effective means of enforcing International Humanitarian Law. Honouring the work of Timothy McCormack, Professor of International Law at the University of Melbourne and a world renowned expert on IHL and International Criminal Law, contributors of the book explore the interplay between the rules governing accountability for violations of IHL and other areas of law that impact the prosecution of war crimes, including international criminal law, human rights law, arms control law, constitutional law and national criminal law.